2021
DOI: 10.1007/s10900-021-01036-6
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination During COVID-19 in a Rural Community: A Cross-sectional Survey

Abstract: Vaccination behavior is an informative metric for assessing flu seasons and is especially important to understand for the 2020–2021 flu season, which coincided with the COVID-19 pandemic. This study aimed to estimate flu vaccine behavior and assess vaccine perceptions during the pandemic season. Using a cross-sectional descriptive study design, we conducted an online survey to assess vaccination behavior and perceptions of both COVID-19 and the flu. Patients were identified as recently seen by providers in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
11
2
Order By: Relevance
“…Vaccine uptake information showed that, although this study was conducted prior to the 2021 flu season, only ~44% of study participants showed predictive flu vaccine acceptance (gets flu vaccine all or most years). This differs from vaccine data gathered in a Central Pennsylvania cohort, which reported a high 88% flu vaccine acceptance rate-highlighting the stark differences that can exist in vaccine uptakes between various Pennsylvania communities and the need for individually assessing smaller local geographical areas (13). Only 54% of participants in the Turtle Creek community had received the COVID-19 vaccine; like in many U.S. communities, this falls short of the national vaccine acceptance rate considered sufficient for herd immunity (described as either >60% or as high as 90% in various studies) (14).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Vaccine uptake information showed that, although this study was conducted prior to the 2021 flu season, only ~44% of study participants showed predictive flu vaccine acceptance (gets flu vaccine all or most years). This differs from vaccine data gathered in a Central Pennsylvania cohort, which reported a high 88% flu vaccine acceptance rate-highlighting the stark differences that can exist in vaccine uptakes between various Pennsylvania communities and the need for individually assessing smaller local geographical areas (13). Only 54% of participants in the Turtle Creek community had received the COVID-19 vaccine; like in many U.S. communities, this falls short of the national vaccine acceptance rate considered sufficient for herd immunity (described as either >60% or as high as 90% in various studies) (14).…”
Section: Discussioncontrasting
confidence: 84%
“…Three separate studies of vaccine hesitancy were conducted in nearby Central Pennsylvania, though all reported significant lack of diversity among sociodemographic groups. Study populations were comprised of 92%-97% non-Hispanic white adults, with the majority having attained high income and educational levels (11)(12)(13). In our study demographic, majority of participants identified as Black or African American (53%), women (81%), having finished high school and/or some post-graduate work but not college (65%), and in the 25-64 age range (78%), largely representative of known Turtle Creek community demographics (7).…”
Section: Discussionmentioning
confidence: 99%
“…Flu vaccine acceptance behavior is known to be influenced by COVID-19. A UK-based national survey reported that the pandemic had motivated unvaccinated people to accept the flu vaccine [ 30 ], while another survey from Pennsylvania, USA, described net favorable changes in flu vaccine acceptance behaviors since the COVID-19 outbreak [ 14 ]. However, when the data from the CDC were analyzed, we found an unchanged flu vaccine acceptance rate since the pandemic outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a US political map with categorical highlights of individual states based on recent flu activity would perhaps be helpful to visualize the variation across the country. This variation in flu activity might be influenced by factors such as nonpharmaceutical interventions [ 12 , 13 ], while flu vaccine acceptance rates could also be another contributor [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in some agreement with other international studies. Domnich et al [20] found that about 20.4% of the Italian adults would not receive the 2020/21 flu vaccine if no COVID-19 pandemic occurred, and Marcus, R.E [39] found that 12.5% of adults in a rural American community changed their flu vaccination plan due to COVID-19. Perceptions of high susceptibility to COVID-19 were also positively associated with pneumonia vaccination uptake in our survey.…”
Section: Discussionmentioning
confidence: 99%